Optimization of Indoor Health and Comfort Based on Greenship Homes 1.0 in Commercial Housing - Yudrika, Nilfa; Irwansyah, Mirza (Riviera Publishing, 2023)
ABSTRACT Aceh high population density causes pressure on the housing sector, and the increasing number of housing developers results in increasingly varied housing types. Royal De' Khansa housing was chosen because it is expected to contribute to sustainable development. CO2 emissions from buildings can have an impact on human health, and Greenship Homes 1.0 is a standardization of the implementation of sustainability practices that can help improve the health and comfort of indoor residential homes. This study aims to calculate the value of IHC criteria in residential houses and provide recommendations for optimizing indoor air quality using qualitative methods and explanatory descriptive approaches. This research was conducted using qualitative methods with a descriptive and explanatory approach. The study grouped the population into a homogeneous classification with all existing houses in the Royal De' Khansa housing. Royal De' Khansa housing types 65 and 85 have met 80% of the IHC category. Types 110 and 120 have met 85% of the IHC category or equivalent to 10 of the 13 IHC points that must be met. Residents are satisfied with this residence in terms of comfort, cleanliness, noise, ventilation, and lighting. The application of GreenSHIP Homes 1.0 in commercial housing in Aceh Besar can provide benefits in optimizing the health and comfort of the room. By meeting 80-85% of the IHC category, Royal De' Khansa housing can provide a healthy and comfortable environment for its residents.